The Maturity Level of IT Governance Based On Cobit Framework 4.0 on DS and ME Domains at PT. Milano Mitra Abadi - Teofilus Sunarsa (Tech-E, 2018)
Milano Mitra Abadi is a retail company engaged in the fashion and shoes in the business process is not separated from the use of IT. IT is an effective step taken by the company to develop its business in order to provide a level of efficiency and effectiveness in the management of sales data or inventory data with good and orderly. One of the tools used for IT Governance is COBIT (Control Objectives for Information and Related Technology) is a standard model that provides documentation of best IT management practices that can help management and user To bridge the gap between business risks, control needs, and technical problems. The analysis for the maturity level is done by comparing the level of maturity that exists at the moment with the level of maturity. The level of maturity that is intended on the basis represents the level of maturity of the industry average at level 3. Current level of maturity (current maturity level) for each process that is in the domain of Deliver and Support and Monitor and Evaluate is almost entirely at level 2. This can be said that the process of IT governance in PT. Milano Mitra Abadi has been done but has not been running optimally, has a pattern that is repeatedly done in conducting activities management related to technology governance Information, but its existence has not been well-defined and formal so that there is still an inconsistency. It is recommended that the evaluation of IT can be done routinely every specific time period (periodically) so that the desired level of maturity can be achieved and performed by a specific unit.